Business Feasibility Analysis of Bioethanol Distillation Equipment Using Waste Empty Palm Oil Bunches and Palm Fronds - Mariyam, Siti; Umam, Muhammad Isnaini Hadiyul; Nur, Muhammad; Suherman, Suherman; Hamdy, Muhammad Ihsan (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
Indonesia as one of the largest palm oil-producing countries in the world, produces a considerable amount of waste as a result of the palm oil production process. It can utilize the waste of empty palm bunches and palm fronds to be used as bioethanol as renewable energy. Purification of bioethanol using distillation equipment. The purpose of this study is to determine the feasibility of bioethanol distillation equipment using waste empty palm bunches and palm fronds in terms of market aspects, technical aspects, and financial aspects. The results of the research based on market aspects with the calculation of the selling price of production, forecasting, and benchmarking are declared feasible to run. Based on the technical aspects of determining the location and production process, it can be declared feasible to run because it is profitable. Based on the financial aspects by calculating NPV of IDR 850,702,895> 0, it is declared feasible because it is positive, PI of 3.67> 1 is declared feasible, IRR of 35%> 11% so that IRR is declared feasible, and PP obtained 2 years 2 months is declared feasible because it can return the investment before 5 years from the time that has been set.